Technical Note: Cumulative dose modeling for organ motion management in MRI‐guided radiation therapy. Issue 2 (20th December 2020) - Mirzapour, Seyed Ali; Mazur, Thomas R.; Harold Li, H.; Salari, Ehsan; Sharp, Gregory C.
Abstract : Purpose: To develop a method for continuous online dose accumulation during irradiation in MRI‐guided radiation therapy (MRgRT) and to demonstrate its application in evaluating the impact of internal organ motion on cumulative dose. Methods: An intensity‐modulated radiation therapy (IMRT) treatment plan is partitioned into its unique apertures. Dose for each planned aperture is calculated using Monte Carlo dose simulation on each phase of a four‐dimensional computed tomography (4D‐CT) dataset. Deformable image registration is then performed both (a) between each frame of a cine‐MRI acquisition obtained during treatment and a reference frame, and (b) between each volume of the 4D‐CT phases and a reference phase. These registrations are used to associate each cine image with a 4D‐CT phase. Additionally, for each 4D‐CT phase, the deformation vector field (DVF) is used to warp the pre‐calculated dose volumes per aperture onto the reference CT dataset. To estimate the dose volume delivered during each frame of the cine‐MRI acquisition, we retrieve the pre‐calculated warped dose volume for the delivered aperture on the associated 4D‐CT phase and adjust it by a rigid translation to account for baseline drift and instances where motion on the cine image exceeds the amplitude observed between 4D‐CT phases. Results: The proposed dose accumulation method is retrospectively applied to a liver cancer case previously treated on an MRgRT platform. Cumulative dose estimated for free‐breathing and respiration‐gated delivery is compared against dose calculated on static anatomy. In this sample case, the target minimum dose and D 98 varied by as much as 5% and 7%, respectively. Conclusion: We demonstrate a technique suitable for continuous online dose accumulation during MRgRT. In contrast to other approaches, dose is pre‐calculated per aperture and phase and then retrieved based on a mapping scheme between cine MRI and 4D‐CT datasets, aiming at reducing the computational burden for potential real‐time applications.